DETERMINAN PROFITABILIAS PT. BANK PANIN DUBAI SYARIAH TBK PERIODE 2013-2017 MENGGUNAKAN METODE ARDL-ECM - Saputra, Donny Eka; Pujiyono, Arif (Diponegoro Journal of Islamic Economics and Business, 2021)
Profitability is an important tool to improve Islamic bank performance, evaluating their operations, determining management policy, making strategy to help the Islamic banks survive in competitive market, and improving living standard of people. In 2017, PT Bank Panin Dubai Syariah Tbk becomes the most losses Islamic bank among the other 14 Islamic bank in Indonesia. This study aims to examine the influence of bank specific and macroeconomy factors that contributed toward the profitability of PT. Panin Dubai Bank Syariah. Tbk over the period 2013- 2017. This study used the Autoregressive Distributed Lag – Error Correction Model (ARDL-ECM) consisting of a stationary test, optimal lag selection, cointegration test, diagnostic test, and stabilization test. Data used in this study are monthly time series data with 60 observations obtained from Otoritas Jasa Keuangan and Badan Pusat Statistik over the period 2013-2017. Bank specific variable are FDR and DPK, while macroeconomic variable are BI Rate, inflation, and exchange rates. Based on optimal lag selection, ARDL (1,0,1,0,0,0) model is generated. The ARDL-ECM estimation results showed that FDR, BIR, and KURS affect profitability in both short and long run. DPK affect profitability only in short run, while inflation does not affect profitability in both short run and long run. The speed of adjustment is 85% per period. The implication of this result is PT. Panin Dubai Bank Syariah Tbk needs to raise CASA to minimalize the operating costs and must able to managed well bad financing through inter-bank, central bank and securities placements.